2004
DOI: 10.2514/4.866760
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Rocket Thrust Chambers

Abstract: Downloaded by PURDUE UNIVERSITY on July 27, 2015 | http://arc.aiaa.org |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 313 publications
0
8
0
Order By: Relevance
“…The transition region becomes wider with increasing pressure, but it degenerates to a sharp interface when the pressure decreases to a subcritical value. For p 100 atm, the upper and lower bounds of density for the transition region are 645 and 450 kg∕m 3 , respectively. Figure 5 shows the temporal evolution of the density fields on three different transverse planes along the axial axis from the vortex chamber to the discharge nozzle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition region becomes wider with increasing pressure, but it degenerates to a sharp interface when the pressure decreases to a subcritical value. For p 100 atm, the upper and lower bounds of density for the transition region are 645 and 450 kg∕m 3 , respectively. Figure 5 shows the temporal evolution of the density fields on three different transverse planes along the axial axis from the vortex chamber to the discharge nozzle.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the underlying flow physics, hydrodynamic waves in the axial and azimuthal directions are analyzed separately. Figure 11 shows the temporal evolution of the density isosurface at ρ 532 kg∕m 3 , located in the interfacial layer between the liquid and gaseous oxygen (see Fig. 2).…”
Section: Flow Instability and Wave Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction S WIRL injectors are widely used to achieve efficient mixing and combustion in propulsion and power-generation systems, including airbreathing engines [1,2] and liquid rockets [3]. The swirling motion of the injected fluid can improve flame stability by producing toroidal recirculation zones and reduce combustion length by inducing high rates of entrainment of the ambient fluid and fast mixing [4].…”
mentioning
confidence: 99%
“…Mills et al 68 reported that, due to the nature of hypergolic propellants, low activation energies are involved, which leads to the formation of many complex intermediates. Interestingly, ammonium nitrate formed only during steady-state operation.…”
Section: Preignition and Preignition Productsmentioning
confidence: 99%